Six new epibiotic Proschkinia (Bacillariophyta) species and new insights into the genus phylogeny. Issue 4 (2nd October 2019) - Majewska, Roksana; Bosak, Sunčica; Frankovich, Thomas A.; Ashworth, Matt P.; Sullivan, Michael J.; Robinson, Nathan J.; Lazo-Wasem, Eric A.; Pinou, Theodora; Nel, Ronel; Manning, Schonna R.; Van de Vijver, Bart
ABSTRACT: The diatom genus Proschkinia is a common element of biofilms covering diverse substrata in saline inland or shallow coastal environments. It can be distinguished from other naviculoid taxa by its lanceolate valves with a fistula located within the central area and numerous open girdle bands with a U-shaped cross-section and a single row of perforations on the internal side of the fold. Despite this distinct morphology, frustules of Proschkinia are typically weakly silicified and often overlooked when cleaned diatom material is analysed. The current paper describes six new species of Proschkinia : P. browderiana sp. nov., P. lacrimula sp. nov., P. maluszekiana sp. nov., P. sulcata sp. nov., P. torquata sp. nov. and P. vergostriata sp. nov., found in numerous samples of marine organisms, such as sea turtles (including sea turtle museum specimens), sea turtle-associated barnacles and seagrass from across the three oceans. Some of the newly described taxa were found on multiple individuals belonging to different sea turtle species, whereas others were in samples collected from different continents. Molecular phylogenetic analysis indicated that examined Proschkinia strains formed a monophyletic clade, sister to Fistulifera .